2022
DOI: 10.3389/fcvm.2022.826630
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor Necrosis Factor Associated Factors (TRAFs) in Vascular Inflammation and Atherosclerosis

Abstract: TNF receptor associated factors (TRAFs) represent a family of cytoplasmic signaling adaptor proteins that regulate, bundle, and transduce inflammatory signals downstream of TNF- (TNF-Rs), interleukin (IL)-1-, Toll-like- (TLRs), and IL-17 receptors. TRAFs play a pivotal role in regulating cell survival and immune cell function and are fundamental regulators of acute and chronic inflammation. Lately, the inhibition of inflammation by anti-cytokine therapy has emerged as novel treatment strategy in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 195 publications
(261 reference statements)
0
11
0
Order By: Relevance
“…Through RNA-seq, we found the expression of several genes involved in inflammatory pathways, especially the TNF signaling pathway and Toll-like receptor signaling pathway manifested distinct changes, among which the TNF receptor associated factors (TRAFs) family, the chemokine CXC motif ligands (CXCLs) family, and IL1 receptor-like 1 (IL1RL1) draws our great attention. TRAF3 is a kind of cytoplasmic signaling adaptor protein that participates in the signal transduction of several important inflammatory pathways, such as NF-κB pathways, TNF signaling pathway, and Toll-like receptor signaling pathway, thus playing a pivotal role in regulating cell proliferation, apoptosis, and inflammatory response ( Häcker et al, 2011 ; Zhou et al, 2021 ; Gissler et al, 2022 ; Wu et al, 2022 ). It was reported that the expression of CXCL10 manifested a positive correlation with the severity of IVDD due to its chemotactic function of recruiting immune cells ( Jacobsen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through RNA-seq, we found the expression of several genes involved in inflammatory pathways, especially the TNF signaling pathway and Toll-like receptor signaling pathway manifested distinct changes, among which the TNF receptor associated factors (TRAFs) family, the chemokine CXC motif ligands (CXCLs) family, and IL1 receptor-like 1 (IL1RL1) draws our great attention. TRAF3 is a kind of cytoplasmic signaling adaptor protein that participates in the signal transduction of several important inflammatory pathways, such as NF-κB pathways, TNF signaling pathway, and Toll-like receptor signaling pathway, thus playing a pivotal role in regulating cell proliferation, apoptosis, and inflammatory response ( Häcker et al, 2011 ; Zhou et al, 2021 ; Gissler et al, 2022 ; Wu et al, 2022 ). It was reported that the expression of CXCL10 manifested a positive correlation with the severity of IVDD due to its chemotactic function of recruiting immune cells ( Jacobsen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TRAF3 prevents CD40-induced endothelial cell activation and inhibits the expression of pro-inflammatory cytokines ( Urbich et al, 2001 ). It seems that TRAF4 does not affect the immune cell development and is not involved in vascular inflammation and/or atherosclerosis ( Gissler et al, 2022 ). TRAF4 is involved in more developmental processes like the formation of the respiratory upper tract ( Shiels et al, 2000 ).…”
Section: Cd40l Signaling Cascade In Atherosclerosis and Its Link To R...mentioning
confidence: 99%
“…TRAF6 also promotes JNK and p38 MAPK signaling cascades through binding to TRAF2 ( Baud et al, 1999 ). The deficiency of TRAF6 in mice has a serve impact of the immune system: mice lacking TRAF6 show inflammatory cell accumulation in organs, thymic atrophy as well as lack of secondary lymphatic organs ( Akiyama et al, 2005 ; Gissler et al, 2022 ). The lack of CD40-TRAF6 binding leads to reduced inflammatory cytokine production resulting in the ameliorated progression of atherosclerosis compared to CD40-TRAF2/3/5 deficient mice.…”
Section: Cd40l Signaling Cascade In Atherosclerosis and Its Link To R...mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, seven members numbered sequentially TRAF1 through TRAF7, have been identified in the TRAF family. TRAF molecules are a family of signaling adapters that play vital roles in regulating cellular signaling not only by members of the TNFRSF and the Toll-like receptor (TLR)/interleukin-1 (IL-1) receptor superfamily but also by unconventional receptors for cytokines including IL-6 [2][3][4][5][6][7][8]. Unlike the non-conventional TRAF7, TRAF1 to TRAF6 share the conserved C-terminal TRAF domain, which binds to the cytoplasmic domains of a range of cell surface receptors (Figure 1).…”
Section: Introductionmentioning
confidence: 99%